The Approach of An Intelligent System for Stopping the Phenomenon of Migration of Young People During the Economic Crisis - Petronela Daniela Feraru (CES Working Papers, 2012)
This study identifies and proposes the approach of a new intelligent system regarding stopping the phenomenon of migration of young people during the current economic crisis. We investigate the manner in which the labour market and the educational system in Romania can contribute to the option of emigration as the only saving opportunity for more and more young people. The economic crisis influences the social-economic development and has a major impact on the decision of young people to migrate from Romania to those countries that may offer a general framework optimum for their future human and professional development. The objectives refer to the assessment of the tendencies of the migration phenomenon and to the analysis of the impact for the educational system. In the end, possible solutions are searched for the identified problems, with the purpose of drawing attention to the loss of our country, due to the migration of the most important segment of the labour market in Romania: the young people. The inductors of migration among young people are the professional-educational factors motivated by the wish to attend a form of higher education and the aspiration to a profession according to their formation. The impact of this study is produced in practice, through the results and conclusions of the analysis carried out.
Keywords: F22; I24; J61; 330; migration; brain migration; economic crisis; labour market; unemployment; competences; human development Romania